INFLUENCE USE DIGITAL TECHNOLOGY AGAINST EFFICIENCY WITH INTERVENING SATISFACTION EMPLOYEES ON PROJECTS CONSTRUCTION INFRASTRUCTURE MINING - Irfan, Irfan; Nurwulandari, Andini (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
In this twenty-first century, the development of digital technology is increasingly diverse and able to contribute to achieving the goals of each individual or group so it is undeniable that technological developments have had a significant impact on Human Resource Management (HRM) in various aspects. Information and communication technology has increased efficiency and effectiveness in the recruitment process, training, employee development, and daily operations through automation, the use of big data, and online platforms, according to (Laura, Lee, Pranoto, Gunawan, Lim, Fransisca, Widya, Christine 2024). Several companies have been affected by the Covid-19 virus pandemic, as a result, all companies have to adjust their strategies, and most companies make internal factors a top priority. The purpose of this research article is to explore more deeply the role of using digital technology, such as digital project management systems including Digital Financial Innovation (DFI) that affect efficiency in mining infrastructure construction projects through intervening Employee Satisfaction influenced by management valence as moderation by using data collection methods in two ways, namely collecting the latest research literature with several international journals from 2020 to 2024 that examine the use of digital technology, Employee Satisfaction, efficiency and Management Valence and using the second method, namely data collection by conducting direct interview techniques with several employees representing mining infrastructure construction projects selected randomly. The results of the analysis show that it is essential to think about the use of digitalization that forms job satisfaction so that it can affect cost efficiency with management valence moderation, the use of digital technology will be able to improve performance and provide various cost and efficiency benefits, including digital systems with the job order or Job Number method, users can increase effectiveness and efficiency in project management so that productivity is increased and the risk of errors due to repeated data input can be reduced. suggestions/implications that may be useful as follows: a) Further research needs to be conducted by adding several external factors that will affect Employee Satisfaction and efficiency. b) From the results of this descriptive study, it is suggested that further research can be conducted on the situation and conditions of the company's organization and local culture to create better project workforce performance as measured by the level of employee satisfaction.